2021
DOI: 10.3389/fvets.2021.689589
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Slaughter Age on Myosin Heavy Chain Isoforms, Muscle Fibers, Fatty Acids, and Meat Quality in Longissimus Thoracis Muscle of Tibetan Sheep

Abstract: Tibetan sheep is one of the dominant livestock at Qinghai-Tibet Plateau, which is the main food source of local people. In order to investigate the effect of slaughter age on meat quality, fatty acid profile and expression of myosin heavy chain (MyHC) isoform genes were analyzed in Tibetan sheep. A total of 24 Tibetan sheep including 4 months old (4 m), 1.5 years old (1.5 y), 3.5 years old (3.5 y), and 6 years old (6 y) were randomly selected. The results indicated that the MyHC IIx and MyHC IIb mRNAs increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 53 publications
0
10
0
1
Order By: Relevance
“…Tenderness, according to Zhao et al ( 54 ), is an essential factor for the valuation of meat quality, and it affects consumer purchasing and market acceptability decisions. IMF is influenced by both genetic and environmental factors, depending on species, breed, genotype, muscle type, age, gender, and nutritional status ( 55 , 56 ). Consequently, increasing the level of IMF is fundamental to improving meat quality ( 56 , 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tenderness, according to Zhao et al ( 54 ), is an essential factor for the valuation of meat quality, and it affects consumer purchasing and market acceptability decisions. IMF is influenced by both genetic and environmental factors, depending on species, breed, genotype, muscle type, age, gender, and nutritional status ( 55 , 56 ). Consequently, increasing the level of IMF is fundamental to improving meat quality ( 56 , 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…The different types of muscle fibers are closely related to meat color, tenderness, water-holding, juiciness, and flavor. Our previous study has identified four types of muscle fibers (Types I, IIa, IIx, and IIb) in the LT muscle of the Tibetan sheep at different ages, corresponding to the four myosin heavy chains, MyHC I, MyHC IIa, MyHC IIx, and MyHC IIb, respectively ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…2015), similar respuesta ha sido reportada en ovejas (Bao et al, 2021), lo cual sugiere que la edad y la raza juega un papel importante en la expresión del mensajero.…”
Section: Literatura Citadaunclassified